Stress, coping, and quality of life of medically underserved lung and head-and-neck cancer patients - Peterson, Grace Elaine Barbara, author; Prince, Mark, advisor; Borrayo, Evelinn, committee member; Henry, Kimberly, committee member; Gonzalez-Voller, Jessica, committee member (Colorado State University. Libraries, 2021)
The intent of this study was to investigate how medically underserved (i.e. uninsured, underinsured, low income) cancer patients responded to a stepped-care cognitive behavioral therapy (CBT) intervention aimed at increasing their ability to cope. The Transactional Model of Stress and Coping (TMSC) was utilized as a theoretical guide to assess outcomes of change in perceived stress, change in coping self-efficacy, and change in general quality of life. A parallel indirect effects model of change scores was tested to assess if this model was a good fit for the data, and results indicated that there was a significant specific direct effect from treatment to change in general quality of life, via change in coping self-efficacy. Further, 40 percent of the variance in change in general quality of life was accounted for by this model, which is a very large effect. Conclusions from this study include the utility of the TMSC to theoretically organize the relations of these outcome variables for lung, head and neck, and thyroid cancer patients who are medically underserved. In addition, this study indicated that the stepped-care CBT intervention increased quality of life for those in the intervention group. Future research should continue to assess for the mental health needs of this specific patient population. Continued resources should be put toward research on the development and implementation of stepped-care therapeutic interventions that increase patient coping skills and thereby increase patient quality of life.
Keywords: coping; quality of life; underserved; lung cancer; cognitive behavioral therapy (CBT); stepped-care